2018
DOI: 10.1021/jacs.8b08653
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Glycoprotein Quality Control System with a Series of Chemically Synthesized Homogeneous Native and Misfolded Glycoproteins

Abstract: The glycoprotein quality control (GQC) system in the endoplasmic reticulum (ER) effectively uses chaperone-type enzymes and lectins such as UDPglucose:glycoprotein glucosyltransferase (UGGT), calnexin (CNX), calreticulin (CRT), protein disulfide bond isomerases (ERp57 or PDIs), and glucosidases to generate native-folded glycoproteins from nascent glycopolypeptides. However, the individual processes of the GQC system at the molecular level are still unclear. We chemically synthesized a series of several homogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Having concluded that UGGT's promiscuity is not dependent on the flexible linker between the catalytic domain and the N-terminal misfold sensing region, but is likely underpinned by the motions uncovered by the MD simulations, the question remains regarding UGGT's reported ability to survey not only folding of small-and medium-size glycoprotein monomers, but also quaternary structure of glycoprotein oligomers and larger multi-glycoprotein complexes [23] [24] [25]. The Indeed, the MD conformational landscape observed in this work reaches extremely compact conformations, which may explain the activity of the enzyme against synthetic glycopeptides [16][17][18][19][20]. Importantly, monomeric UGGT can recognize and re-glucosylate a misfolded glycoprotein only if it can bridge the distance between a folding defect and at least one of the glycoprotein's N-linked glycosylation sites.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Having concluded that UGGT's promiscuity is not dependent on the flexible linker between the catalytic domain and the N-terminal misfold sensing region, but is likely underpinned by the motions uncovered by the MD simulations, the question remains regarding UGGT's reported ability to survey not only folding of small-and medium-size glycoprotein monomers, but also quaternary structure of glycoprotein oligomers and larger multi-glycoprotein complexes [23] [24] [25]. The Indeed, the MD conformational landscape observed in this work reaches extremely compact conformations, which may explain the activity of the enzyme against synthetic glycopeptides [16][17][18][19][20]. Importantly, monomeric UGGT can recognize and re-glucosylate a misfolded glycoprotein only if it can bridge the distance between a folding defect and at least one of the glycoprotein's N-linked glycosylation sites.…”
Section: Discussionmentioning
confidence: 94%
“…Since the discovery of UGGT back in 1989 [11,12], activity studies have used a range of glycoprotein substrates, such as urea-misfolded bovine thyroglobulin [11], mutants of exo-(1,3)-β-glucanase [13], RNase BS [14,15], small size synthetic compounds bearing high-mannose glycans attached to fluorescent aglycon moieties such as 'TAMRA' and 'BODIPY' [16,17] and chemically synthesized misfolded glycoproteins [18][19][20], to mention only a few. Although a comprehensive list of physiological UGGT substrate glycoproteins has not been compiled, and the molecular detail on UGGT:substrate interactions remains uncharacterized, it is apparent that the enzyme is highly promiscuous.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of UGGT in 1989 (Parodi, 2007;Trombetta et al, 1989), UGGT activity studies have used a range of glycoprotein substrates (Trombetta et al, 1989;Taylor et al, 2004;Ritter and Helenius, 2000;Ritter et al, 2005), small-size glycosylated synthetic compounds (Totani et al, 2006(Totani et al, , 2009, and chemically synthesized misfolded glycoproteins (Izumi et al, 2016a(Izumi et al, , 2016bKiuchi et al, 2018). In addition to glycoprotein monomers, UGGT also surveys the quaternary structure of glycoprotein oligomers and larger multi-glycoprotein complexes (Keith et al, 2005;Zhang et al, 2011;Gardner and Kearse, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of UGGT in 1989 (Parodi, 2007;Trombetta et al, 1989), UGGT activity studies have used a range of glycoprotein substrates (Trombetta et al, 1989;Taylor et al, 2004;Ritter and Helenius, 2000;Ritter et al, 2005), small-size glycosylated synthetic compounds (Totani et al, 2006(Totani et al, , 2009, and chemically synthesized misfolded glycoproteins (Izumi et al, 2016a(Izumi et al, , 2016bKiuchi et al, 2018). In addition to glycoprotein monomers, UGGT also surveys the quaternary structure of glycoprotein oligomers and larger multi-glycoprotein complexes (Keith et al, 2005;Zhang et al, 2011;Gardner and Kearse, 1999).…”
Section: Discussionmentioning
confidence: 99%